MENYELESAIKAN MASALAH KELUARGA TANPA MELAKUKAN TINDAKAN KEKERASAN DALAM RUMAH TANGGA BERDASARKAN U.U. NOMOR 23 TAHUN 2003 TENTANG KDRT - Muzayanah Muzayanah (Jurnal Pengabdian Kepada Masyarakat Media Ganesha FHIS, 2022)
In living household and family life, of course, it is never separated from the problems that arise in the family itself. Every family member has rights and obligations that are protected by the state with the enactment of statutory provisions because Indonesia is a state of law. Rights and obligations that must be upheld by every human being within the family sphere, so it is necessary to foster legal awareness and public obedience to applicable laws. For this reason, so that the implementation of the Law on Domestic Violence (KDRT) will be successful, I hope that the residents of Prolanis Clinic "RAHMATIKA" are able to understand and implement the contents of the U.U. Number 23 of 2004 concerning Domestic Violence. This legal counseling is very important for the residents of Prolanis, because with this legal counseling it is hoped that every family, especially husband and wife and family members in the household will always understand the provisions of this Law on Domestic Violence which regulates the prescribed legal sanctions, so that every family members if there are problems in the household do not solve the problem by committing violence, so they take actions that are contrary to the provisions stipulated in the law about Domestic Violence (KDRT). This legal counseling was given to residents of the Prolanis Clinic "RAHMATIKA" Gunung Pati Semarang by providing counseling materials and holding a question-and-answer session. Participants are very enthusiastic in participating in this legal counseling, because this counseling is an educational program programmed for Prolanis Participants with BPJS facilities. This legal counseling is very important for the Prolanis residents, considering that problems in the household are not only experienced by young families, but also experienced by households or families for those who are of advanced age. Considering that life will continue for a lifetime, of course the problems faced in the household will also continue to roll and survive that life also takes place. Of course, to solve each problem it must be resolved by the disputing parties in the household, it's just that in solving problems in the household it should be done by not committing domestic violence. There are many ways to solve problems properly, without committing domestic violence, because violence certainly will not solve problems in the household itself.